Do Political Connections Weaken Tax Enforcement Effectiveness? - Lin, Kenny Z.; Mills, Lillian F.; Zhang, Fang; Li, Yongbo (Contemporary Accounting Research, 2018)
ABSTRACT This paper examines whether ties to politicians by corporate boards of directors weaken the effectiveness of tax authorities in constraining tax avoidance in China. We use a unique data set to measure geographic time‐variant tax enforcement, including the probability of income tax audit, the expertise of tax officers, and the consequences of underreporting tax liabilities. Based on a sample of 11,121 firm‐years from 2003 to 2013, we find that the deterrent effect of the probability that a firm's taxable income understatement will be detected and lead to heavy penalties is significantly undermined if the board is politically connected. To enhance our analysis, we use opportunities for income shifting, the most likely mechanism through which Chinese firms avoid taxes on an ongoing basis, to illustrate how connected boards exert power to unwind the constraining effect of tax enforcement. Overall, our results suggest that a board's ties to politicians can be a significant challenge to the effective enforcement of tax compliance in a politically controlled economy.